2020
DOI: 10.1016/j.redox.2020.101723
|View full text |Cite
|
Sign up to set email alerts
|

Elevated 4-hydroxynonenal induces hyperglycaemia via Aldh3a1 loss in zebrafish and associates with diabetes progression in humans

Abstract: Increased methylglyoxal (MG) formation is associated with diabetes and its complications. In zebrafish, knockout of the main MG detoxifying system Glyoxalase 1, led to limited MG elevation but significantly elevated aldehyde dehydrogenases (ALDH) activity and aldh3a1 expression, suggesting the compensatory role of Aldh3a1 in diabetes. To evaluate the function of Aldh3a1 in glucose homeostasis and diabetes, aldh3a1 −/− zebrafish mutants were generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 68 publications
0
48
0
Order By: Relevance
“…Therefore, 4-HNE in VAT is related to VAT dysfunction and oxidative stress even at low BMI, leading to restricted lipid buffering function of adipose tissue and increased lipid peroxidation as a function of BMI increase. In T2DM patients, higher serum levels of 4-HNE were found to directly correlate with clinical prognostic parameters (glycated hemoglobin, fasting glucose) [ 66 ]. However, the role of 4-HNE in metabolic diseases has not yet been fully elucidated and is probably concentration-dependent.…”
Section: Redox Diseases Need Redox Biomarkersmentioning
confidence: 99%
“…Therefore, 4-HNE in VAT is related to VAT dysfunction and oxidative stress even at low BMI, leading to restricted lipid buffering function of adipose tissue and increased lipid peroxidation as a function of BMI increase. In T2DM patients, higher serum levels of 4-HNE were found to directly correlate with clinical prognostic parameters (glycated hemoglobin, fasting glucose) [ 66 ]. However, the role of 4-HNE in metabolic diseases has not yet been fully elucidated and is probably concentration-dependent.…”
Section: Redox Diseases Need Redox Biomarkersmentioning
confidence: 99%
“…The gene is available in human, mouse, and zebrafish. In zebrafish, the gene shares 61.6% to human ALDH3A1 (Lou et al, 2020 ). Lou et al ( 2020 ) revealed that aldh3a1 −/− knockout in zebrafish is accompanied with an increased whole larval glucose, retinal vasodilatory alterations, and generally impaired glucose metabolism.…”
Section: Methods/models Of Inducing Hyperglycemia In Zebrafishmentioning
confidence: 99%
“…In zebrafish, the gene shares 61.6% to human ALDH3A1 (Lou et al, 2020 ). Lou et al ( 2020 ) revealed that aldh3a1 −/− knockout in zebrafish is accompanied with an increased whole larval glucose, retinal vasodilatory alterations, and generally impaired glucose metabolism. They also showed a correlation between HbA1c increase and 4-hydroxynonenal (4-HNE).…”
Section: Methods/models Of Inducing Hyperglycemia In Zebrafishmentioning
confidence: 99%
See 2 more Smart Citations